Menggali Potensi Nilai-Nilai Sosial Dalam Tradisi Maccerak Parek Masyarakat Bugis Tanjung Jabung Timur Jambi - Haeran Haeran; Baso Iping (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The tradition of maccérak pãrek is one of the traditions that is still carried out by the Bugis tribe community in Tanjung Jabung East is the tradition of Maccérac Pãrek. The purpose of research is to find social values in the tradition of maccérak parrek. The results of the research obtained are that the tradition of maccérak pãrek, maccèrak kampong or often also called massalama’ kampong is an annual tradition of the Bugis community in Tanjung Jabung East. This tradition is a people's feast, to cleanse the village to reject the blasphemy or to throw away the damn thing. In addition to having a spiritual function, the implementation of the tradition serves as an embodiment of joy, thanksgiving to the One God for the gift of abundant produce and avoidance of calamity while seeking food. The conclusion of this study is that the tradition of Maccérak parrek for the Bugis community in Tanjung Jabung East is not just an annual event of a folk party aimed at cleansing the village to reject the damn or to throw away the goddamn, but there are social values in it that are interesting to study.